Environmental Management in Swedish Construction Projects – Actors, Tools, Incentives and Development - Koppfeldt, Anders; Revellé, Jakob (My University, 2017)
Environmental sustainability has been given increased focus during the later years and technical solutions and management practices have therefore been applied. Environmental Management Systems are today present in almost every larger company in the Swedish construction industry as the companies strive to stay competitive on the market. To enhance the environmental work and to market projects, environmental certifications are commonly applied on various projects. The purpose of this thesis is to investigate the status of the environmental work and processes related, in the Swedish construction industry. It is an abductive and qualitative study including both a literature review and interviews within the Swedish construction sector. The results from the empirics are compared with theory as well as other studies performed within the same research area. It was concluded that there is an ongoing development in environmental sustainability. Further, the consensus between the respondents was overall great in many of the aspects about challenges and possibilities. A need for broad collaboration across roles and actors in these complex matters were evident.
Keywords: Samhällsbyggnadsteknik; Civil Engineering